Associations between dyslipidaemia and pregnancy outcomes in the first complete cycle of IVF/ICSI: a real-world analysis. Issue 6 (December 2021) - Yang, Tianli; Zhao, Jing; Zhang, Qiong; Liu, Donge; Liu, Nenghui; Li, Yumei; Yao, Zhongyuan; Zhang, Yeqing; Tian, Fen; Liao, Tingting; Tang, Hongying; Li, Yanping
Abstract: Research question: Are there associations between dyslipidaemia and pregnancy outcomes in the first complete cycle of IVF/intracytoplasmic sperm injection (ICSI)? Design: This long-term, retrospective real-world analysis involved 5030 infertile women who underwent a first complete IVF/ICSI cycle between January 2015 and October 2020. They were categorized into dyslipidaemia ( n = 1903) and control ( n = 3127) groups according to serum lipid concentrations before ovarian stimulation. Propensity score matching and multivariable logistic regression were used to control for confounding variables. Results: In the raw cohort, women with dyslipidaemia had a significantly increased late miscarriage rate ( P = 0.039), decreased term birth rate ( P = 0.002) and decreased live birth rate ( P = 0.005) compared with non-dyslipidaemic women. In the propensity score-matched cohort, the term birth rate ( P = 0.038) and live birth rate ( P = 0.044) were significantly lower in the dyslipidaemia group ( n = 1686) than the controls ( n = 1686). Multivariable logistic regression indicated that infertile women with dyslipidaemia ( P = 0.026) and elevated serum total cholesterol concentrations (total cholesterol ≥5.20 mmol/l; P = 0.028) were significantly less likely to have a live birth. Rates of late miscarriage ( P = 0.027), term birth ( P = 0.003) and live birth ( P = 0.010) differed significantly among women with normal, borderline increased and increased serum lipid concentrations. Compared with controls, women with increased serum lipid concentrations had a significantly higher late miscarriage rate, lower term birth rate and lower live birth rate. Women with increased serum lipid concentrations were significantly less likely than controls to have a live birth. Conclusions: Dyslipidaemia, total cholesterol ≥5.20 mmol/l and degrees of elevated serum lipid concentrations are negatively associated with live birth rate in the first complete IVF/ICSI cycle in infertile women.